Multi-criteria decision making method of minimal suitable values - Žižović Mališa; Damljanović Nada; Nikolić Rale; Vujičić Momčilo (Mathematica Moravica, 2016)
This paper presents a conceptual and mathematical model of a multi-criteria decision making process in which the information about decision maker's preferences is expressed in the form of minimal suitable values.